Current state and development tendency of insurance (Вестник КазНУ. Серия Экономическая, 2016)
This article deals with themodern stage and problems of develop- modern stage and problems of develop- modern stage andproblems of develop- problems of develop-ment of insurance in the Republic of Kazakhstan.In the article is given the evaluation of national insurance market for the last 5 years. And is provided withcomparative analysis of a condition of insurance in the developed countries, such as China, USA and the Russia.Also is made a structural analysis of the volume of insurance premiumand insurance payments for 2012-2013 years.As a research result the reasons of back- As a research result the reasons of back-wardness of this sector are revealed and recommendations about their elimination are made.
Keywords: insurance; insurer; contribution; assets; services; market; company; policy; resources; population